A new toxin delivery device for stoats—results from a pilot field trial. Issue 3 (3rd July 2018) - Murphy, Elaine; Sjoberg, Tim; Dilks, Peter; Smith, Des; MacMorran, Duncan; Aylett, Paul; Ross, James
ABSTRACT: Stoats ( Mustela erminea ) were introduced to New Zealand to control rabbits in the 1880s and their impact on native birds has been devastating. Stoat control needs to be ongoing if some iconic species are to survive on the mainland. A re-setting toxin device (Spitfire) has been developed that fires a paste containing para-aminopropiophenone (PAPP) on to the belly of stoats as they pass through a tunnel. When the stoats groom the paste from their fur, they ingest the toxin. A pilot field trial of the device was undertaken in the Blue Mountains, West Otago in late 2013. The probability of detecting stoats using camera traps declined by between 76.6% and 89.8% within 6 weeks following the deployment of the Spitfire; however, by this time, some of the Spitfires had malfunctioned. Spitfires could be a useful additional control tool for stoats, but they need to be re-engineered to be made more durable for field conditions.